2021
DOI: 10.3389/fphar.2021.744578
|View full text |Cite
|
Sign up to set email alerts
|

YRDC Mediates the Resistance of Lenvatinib in Hepatocarcinoma Cells via Modulating the Translation of KRAS

Abstract: Lenvatinib is the latest and promising agent that has demonstrated a significant improvement of progression-free survival in advanced hepatocellular carcinoma (HCC). However, resistance emerges soon after initial treatment, limiting the clinical benefits of lenvatinib. Therefore, understanding the mechanism of resistance is necessary for improving lenvatinib efficacy. YRDC promotes the proliferation of hepatocarcinoma cells via regulating the activity of the RAS/RAF/MEK/ERK pathway, which was the primary pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 51 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…Previous studies have reported that YRDC regulates RNA translation via involvement in tRNA’s N6-threonyl carbamoyl adenosine (t 6 A) synthesis(El Yacoubi et al, 2009; Lescrinier et al, 2006; Murphy et al, 2004), and it has been reported that can regulate HCC cell resistance to lenvatinib by regulating KRAS translation(Guo et al, 2021). In our study, we found that YRDC has a higher translation efficiency in EGFR-TKI resistant cells than sensitive cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that YRDC regulates RNA translation via involvement in tRNA’s N6-threonyl carbamoyl adenosine (t 6 A) synthesis(El Yacoubi et al, 2009; Lescrinier et al, 2006; Murphy et al, 2004), and it has been reported that can regulate HCC cell resistance to lenvatinib by regulating KRAS translation(Guo et al, 2021). In our study, we found that YRDC has a higher translation efficiency in EGFR-TKI resistant cells than sensitive cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…YRDC is involved primarily in adenosine 37 N 6 -threonyl-carbamoylation in tRNA’s ANN-type tRNAs (t 6 A) synthesis for recognizing ANN codons(El Yacoubi et al, 2009). t 6 A represents the widely distributed modification necessary to maintain the accurate and efficient translation(Lescrinier et al, 2006; Murphy et al, 2004), and YRDC regulates HCC cell resistance to lenvatinib by regulating KRAS translation(Guo et al, 2021). The present work found that YRDC facilitates EGFR-TKIs resistance in NSCLC cells, and the RNA structure in 3’ UTR of YRDC mRNA can modulate translation efficiency, which only exists in PC9 cell that is sensitive to EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…All the primers were produced by Shanghai Sangon Biotech Co., Ltd, Shanghai, China. The qPCR was performed as described ( 32 ). Data were analyzed using the -ΔCt method and the expression of β-actin was used as normalization control.…”
Section: Methodsmentioning
confidence: 99%
“…It also promotes the proliferation of HCC cells by regulating the activity of the RAS pathway—the primary pathway impacted by the anticancer effects of lenvatinib. Notably, YRDC was found to mediate the resistance of lenvatinib in HCC cells by modulating translation of the proto-oncogene K-Ras [ 158 ]. Consistent with this, YRDC has been confirmed as a potential predictive biomarker of lenvatinib sensitivity in HCC.…”
Section: Genes Associated With Lenvatinib Resistancementioning
confidence: 99%